Identification, risk stratification and prognostication of stroke by detection of intra-carotid plaque hemorrhage. (11th May 2021) - Maqsood, H; Younus, S; Saim, M; Qazi, S; Basit, A; Shakeel, HA
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Atherosclerotic stenosis of the internal carotid artery is present in 1% to 2% of the adult population and is the cause of  10% to 15% of ischemic strokes. Intra-plaque hemorrhage (IPH) in carotid stenosis increases the risk of cerebrovascular events. Magnetic resonance imaging can be used to detect pathologies like IPH and necrosis in carotid stenosis. Purpose  : This study sought to compare the risk of stroke between patients with carotid artery disease with and without the presence of intraplaque hemorrhage (IPH) on magnetic resonance imaging. Methods  : In this meta-analysis we gathered the data from 10 original cohort studies including 631 patients with symptomatic carotid stenosis and 157 patients with asymptomatic carotid stenosis. Primary outcome was the hazards of ipsilateral ischemic stroke which were compared between patients with and without IPH. Results  : IPH was present in 57.1% of patients with symptomatic carotid stenosis and 24.7% of patients with asymptomatic carotid stenosis. During 1, 334 observed person-years, 74 ipsilateral strokes occurred. Presence of IPH at baseline increased the risk of ipsilateral stroke both in symptomatic (hazard ratio [HR]: 11.7; 95% confidence interval [CI]: 4.7 to 22.8) and asymptomatic (HR: 6.8; 95% CI: 0.9 to 45.4) patients. Multivariate analysis identified IPH (HR: 11.7; 95% CI: 5.3 to 26.4) and severe degree of stenosis (HR: 3.8; 95% CI: 02 to 8.2) as independent predictors of ipsilateral stroke. Conclusion  : Our study concludes that IPH is common in patients with carotid artery stenosis and is a stronger predictor of stroke. Magnetic resonance imaging is the modality that can help in identification of patients with carotid disease who would benefit from revascularization.